Measuring the design of empathetic buildings: a review of universal design evaluation methods. (2nd January 2016) - O Shea, Eoghan Conor; Pavia, Sara; Dyer, Mark; Craddock, Gerald; Murphy, Neil
Abstract: Purpose : Universal design (UD) provides an explanation of good design based on the user perspective, which are outlined through its principles, goals, and related frameworks. The aim of this paper is to provide an overview of the frameworks and methods for UD building evaluations and to describe how close they have come to describing what a universally designed building is. Methods : Evaluation approaches are reviewed from the existing literature across a number of spatial disciplines, including UD, human geography and urban studies. Results : Four categories of UD evaluation methods are outlined, including (1) checklist evaluations, (2) value-driven evaluations, (3) holistic evaluations, and (4) invisible evaluations. Conclusions : A number of suggestions are made to aid research aimed at developing UD evaluation in buildings. (1) Design standards and guidelines should be contested or validated where possible; (2) evaluation criteria should be contextual; (3) it may be more practical to have separate methodologies for contextualising UD to allow for the creation of an evaluating tool that is practical in use. Additionally, there is a difficulty in establishing a clear basis for evaluating how empathetic buildings are without expanding the methodological horizons of UD evaluation. Implications for Rehabilitation: For universal design (UD) evaluation to address human need requires methods that are culturally, temporally, and typologically specific. Practical instruments for measuring UD need to be divorced from but contingent upon methods than can address local specificities. The process of evaluation can provide knowledge that can contest or validate the literature based sources such as design guidelines, or standards. UD evaluation requires constant renewal by searching for new, flexible strategies that can respond to socio-cultural change.